Local subungual excision and graft use in patients with incontinentia pigmenti: A case report and review of the literature. (March 2017) - Al-Hassani, Fawaz; Davies, James; Pang, Calver; Knight, Simon
Abstract: Incontinentia pigmenti (IP) is a rare genetic skin disorder with an X-linked dominant inheritance that is seen almost exclusively in females. Subungual keratoacanthoma (SUKA) is a rare benign neoplasm of the nail bed associated with IP. The recommended initial treatment of SUKA is conservative thereby sparing the digit in the form of excision and curettage. However, definitive treatment involves terminalisation of the affected digit. We report a case in a 54-year-old woman with IP who developed SUKA who was treated with local subungual excision and subsequent skin grafting who had previous terminalisation of other digits for the same condition. Subungual keratoacanthoma is a rare benign neoplasm that is typically treated with curettage and excision at the initial stages with terminalisation as the definitive treatment. Given the highly positive outcome in this case with minimal sacrifice to the dexterity of the patient and preservation of digit length, we feel that local subungual excision and skin grafting should be strongly considered as an alternative to amputation in moderate to severe cases of the condition.